Blueberry cell wall fractionation, characterization and glycome profiling. (May 2019) - Lin, Zhuangsheng; Pattathil, Sivakumar; Hahn, Michael G.; Wicker, Louise
Abstract: Blueberry powder was sequentially fractionated to water (WSF), chelator (CSF) and sodium carbonate (NSF) soluble fractions. Uronic acid content was above 22 μg/mg AIS. The 4% potassium hydroxide (4KSF) and 24% potassium hydroxide (24KSF) soluble fractions were hemicellulose rich fractions. Cell wall glycan-directed monoclonal antibodies (mAbs) based glycome profiling analyses revealed that WSF, CSF and NSF fractions had epitopes of homogalacturonan (HG), arabinogalactan (AG), and xyloglucan (XG), but no xylan. 4KSF and 24KSF fractions had higher abundance of xyloglucan and xylan epitopes in addition to pectic epitopes. Arabinose and galactose were the two major neutral sugars in the WSF, CSF, and NSF. Xylose represented about 70 mol% neutral sugar in 4KSF and 24KSF fractions. Increased flexibility and presence of protein likely influence the propensity of pectin to bind anthocyanins. Graphical abstract: Image 1 Highlights: Water soluble blueberry fraction has lower than 50% DE. Water soluble fraction is rich in xyloglucans, low in homogalactan. Chelator soluble fraction is rich in xyloglucan, rhamnogalactan and xylan. Protein content is higher in alkali soluble fraction. Increased protein and flexibility of pectin may increase anthocyanin binding.